Causes of Hypertensive Anterior Uveitis in Thailand. (18th May 2020) - Khieu, Chansathya; Kongyai, Natedao; Pathanapitoon, Kessara; Van Der Eijk, Annemiek A.; Rothova, Aniki
ABSTRACT: Purpose: To determine the prevalence of viral infections in patients with hypertensive anterior uveitis in Thailand from polymerase chain reaction (PCR) of aqueous humor. Methods: Thirty-one patients with anterior uveitis with intraocular pressure (IOP) above 25 mmHg were included for PCR analysis for cytomegalovirus (CMV), herpes simplex (HSV), varicella-zoster (VZV), rubella, chikungunya and Zika virus. Results: The prevalence of PCR-positive results was 32%, including 19% for CMV, 10% for HSV, and 3% for VZV; PCR for other tested viruses demonstrated negative results. PCR-positive patients exhibited satisfactory IOP control with antiviral and anti-glaucomatous treatment compared to PCR-negative patients, and more than half of PCR-negative patients required glaucoma surgery within 12 months ( P = .01). Conclusion: PCR evidence of infection with herpes group viruses was found in one-third of patients with hypertensive anterior uveitis; CMV being the most common pathogen. The PCR-positive group generally responded well to a combination of antiviral and anti-glaucoma treatment.